Agricultural correlates of linear growth and key modifiers among children under two years in rural Uganda. - Gunaratna, Nilupa. (Tufts University. Tisch Library., 2017)
This study was a cross-sectional survey that provides a baseline to evaluate a large USAID-funded integrated nutrition and agriculture program called the Community Connector (CC) The study was conducted in three districts designated as CC Phase I and three districts designated as CC Phase II in northern and southwestern Uganda. The target sample size in each district was 600 randomly selected households, for a total target sample size of 3600 households and a final achieved sample size of 3630 households.